Organizing Pneumonia as a Manifestation of AIDS in a Patient With Partially Treated Pneumocystis Jiroveci Pneumonia: Case Report and Literature Review. Issue 6 (November 2020) - Khan, Muhammad Shayan; DeBiase, Joseph Michael; Aouad, Arlette T.
Abstract : Abstract: Organizing pneumonia (OP), formerly called bronchiolitis obliterans organizing pneumonia, is a rare disease characterized by necrotizing granulomas and fibrosis in the small airways of lungs. We arguably present the fourth reported case of a patient with human immunodeficiency virus who was diagnosed with OP in the setting of partially treated Pneumocystis jiroveci pneumonia (PJP). A 59-year-old white man with human immunodeficiency virus and acquired immunodeficiency syndrome had multiple admissions for pneumonia, which was culture negative and partially treated for possible PJP. Eventually, a lung biopsy showed necrotizing OP and fibrosis, typical of OP, with granulomatous features and 3 PJP organisms seen on biopsy. The patient eventually improved with intravenous corticosteroids, whereas primaquine and clindamycin were continued for partially treated PJP. Organizing pneumonia should be considered in immunodeficiency with persistent pulmonary infiltrates not responding to antibiotic therapy. Whether immunodeficiency or infections predispose these patients to OP remains unclear. Prolonged corticosteroids remain the cornerstone of therapy in OP.